1984
DOI: 10.1103/physrevlett.52.1251
|View full text |Cite
|
Sign up to set email alerts
|

Carmeli and Nitzan Respond

Abstract: Carmeli and Nitzan Respond: Recently several workers' have attempted to extend Kramers's theory of activated rate processes to the whole friction range. Buttiker and Landauer express in a recent Comment5 their views on the relation between their work' and ours. Our view is stated here. The theories by Buttiker, Harris, and Landauer (BHL)' and by Carmeli and Nitzan use the same philosophymatching Kramers's energy solution which is valid in the low-friction limit inside the well to another solution valid in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 5 publications
0
71
1
Order By: Relevance
“…Therefore, if the noise source has a nonvanishing correlation time z, the limiting (non-Markovian)master operators of the type in (3.3), (3.4) and (3.10) yield information about quantities which involve zero-modes only; e.g. the stationary probability if(x), or current carrying stationary non-equilibrium probabilities [9][10][11][12], which clearly also do not depend on the initial preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the noise source has a nonvanishing correlation time z, the limiting (non-Markovian)master operators of the type in (3.3), (3.4) and (3.10) yield information about quantities which involve zero-modes only; e.g. the stationary probability if(x), or current carrying stationary non-equilibrium probabilities [9][10][11][12], which clearly also do not depend on the initial preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Kubo [4,7] has shown that a very short correlation time of the fluctuating magnetic field yields a vanishing effect on the motion of the spin; on the contrary, if the fluctuations of the field are large and correlated over a long time scale, the motion of the spin is greately modified. Another important example is the relevant influence of the correlated noise on the activation rates in equilibrium systems [8][9][10][11] and in driven non-equilibrium systems [12]. Generally, the finite correlation of the noise will have an effect on the form of the stationary probability.…”
Section: Introductionmentioning
confidence: 99%
“…͑15͒. In our simulation we employ a local Langevin thermostat with a position-dependent friction [49][50][51][52] …”
Section: ͑15͒mentioning
confidence: 99%
“…Although the accelerated dynamics is advantageous in some cases it can turn out to be problematic if one is really interested in dynamics in situations where two levels of resolutions are used within one simulation, as in the case of AdResS. To overcome this problem one can couple different classes of DOFs to the Langevin thermostat with different friction constants 25,26,27,28 . We have shown in the example of liquid water that the coarse-grained dynamics can be slowed down by increasing the effective friction in the coarse-grained system 29 .…”
Section: Introductionmentioning
confidence: 99%